2020
DOI: 10.1002/pol.20190163
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer onion‐like vesicles self‐assembled from amphiphilic hyperbranched multiarm copolymers via simulation

Abstract: Multilayer onion‐like vesicles are valuable in cell mimics and biomedicine fields. However, as an excellent self‐assembly precursor, the formation of multilayer onion‐like vesicles by the self‐assembly of hyperbranched multiarm copolymers (HMCs) were not reported due to the complex self‐assembly dynamics. In this article, the self‐assembly behavior of multilayer onion‐like vesicles from HMCs was systematically investigated using dissipative particle dynamics simulation. The formation conditions for different k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 73 publications
(95 reference statements)
0
13
0
Order By: Relevance
“…The self‐assembly process of amphiphilic, hyperbranched, multi‐arm copolymers (HMCs) has also been simulated using DPD. [ 60–65 ] The degree of branching greatly influences the self‐assembled structure of HMCs. With the aid of DPD simulations, the study of different branching conditions revealed the self‐assembly mechanism and the kinetic formation process.…”
Section: Application Of Dpd On Mesoscale Properties Of Polymermentioning
confidence: 99%
See 2 more Smart Citations
“…The self‐assembly process of amphiphilic, hyperbranched, multi‐arm copolymers (HMCs) has also been simulated using DPD. [ 60–65 ] The degree of branching greatly influences the self‐assembled structure of HMCs. With the aid of DPD simulations, the study of different branching conditions revealed the self‐assembly mechanism and the kinetic formation process.…”
Section: Application Of Dpd On Mesoscale Properties Of Polymermentioning
confidence: 99%
“…The self‐assembly behavior of multilayer onion‐like vesicles has been systematically investigated as well. [ 62 ] In this study, different numbers of layers were obtained by adjusting the polymer concentration. The results revealed that the onion‐like vesicles have a monolayered structure.…”
Section: Application Of Dpd On Mesoscale Properties Of Polymermentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that the size of dendrimersomes will not increase through mutual fusion once the well-defined onion-like structure is formed, unlike numerous lipidsomes and polymersomes that can spontaneously coalesce. Future work combining their hard chain model with the previous reports using flexible chain models [ 144 , 147 , 148 , 149 , 151 , 152 ] could more fully characterize and predict the potential of dendrimersomes for applications in drug and gene delivery.…”
Section: Polymer-based Smart Nanocarriersmentioning
confidence: 99%
“…Recent interesting work describes the use of dendrimersomes or multilamellar vesicles formed using amphiphilic Janus dendrimers by injecting THF solutions of the dendrimer into water or a buffer. 11 , 12 These are multistep synthetic processes involving the use of organic solvents, and their nontoxicity remains to be determined. Other recent examples include the use of rodlike oligofluorenes in a acetonitrile–water mixed solvent.…”
Section: Introductionmentioning
confidence: 99%